The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12864-016-3321-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating survival time of patients with glioblastoma multiforme and characterization of the identified microRNA signatures

Abstract: BackgroundThough glioblastoma multiforme (GBM) is the most frequently occurring brain malignancy in adults, clinical treatment still faces challenges due to poor prognoses and tumor relapses. Recently, microRNAs (miRNAs) have been extensively used with the aim of developing accurate molecular therapies, because of their emerging role in the regulation of cancer-related genes. This work aims to identify the miRNA signatures related to survival of GBM patients for developing molecular therapies.ResultsThis work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 79 publications
(63 reference statements)
0
28
0
Order By: Relevance
“…Some research have found that miR-657 overexpressed in lung cancer, cervical squamous cell carcinoma, larynx carcinoma, hepatocellular carcinoma, and it can promote carcinoma cells abilities of tumorigenesis, proliferation and invasion by some complex targeting pathways 37,40 . And For miR-587, it can antagonize 5-FU-induced apoptosis and confers drug resistance by regulating PPP2R1B expression in colorectal cancer, and it is related to the survival time of glioblastoma multiforme patients 41,42 . In contrast, mir-1205, miR-637, and miR-548p act as tumor suppressor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Some research have found that miR-657 overexpressed in lung cancer, cervical squamous cell carcinoma, larynx carcinoma, hepatocellular carcinoma, and it can promote carcinoma cells abilities of tumorigenesis, proliferation and invasion by some complex targeting pathways 37,40 . And For miR-587, it can antagonize 5-FU-induced apoptosis and confers drug resistance by regulating PPP2R1B expression in colorectal cancer, and it is related to the survival time of glioblastoma multiforme patients 41,42 . In contrast, mir-1205, miR-637, and miR-548p act as tumor suppressor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The feature selection algorithm IBCGA uses an intelligent evolutionary algorithm 82 to solve the large parameter optimization problem. IBCGA has been successfully applied in several bioinformatics problems, including the prediction of human ubiquitination sites 83 , the prediction of the regulatory roles of cyclic AMP receptor proteins 84 and the estimation of survival time for cancer patients 85 , 86 .…”
Section: Methodsmentioning
confidence: 99%
“…The parameter tuning of IBCGA was same with the previous study 34, 35 . The customized IBCGA for obtaining the m -miRNA signature where r start  ≤  m ≤  r end is described below.…”
Section: Methodsmentioning
confidence: 99%